Collaboration in Giftedness and Talent Development Research. (June 2020) - Makel, Matthew C.; Smith, Kendal N.; Miller, Erin M.; Peters, Scott J.; McBee, Matthew T.
Existing research practices in gifted education have many areas for potential improvement so that they can provide useful, generalizable evidence to various stakeholders. In this article, we first review the field's current research practices and consider the quality and utility of its research findings. Next, we discuss how open science practices increase the transparency of research so readers can more effectively evaluate its validity. Third, we introduce five large-scale collaborative research models that are being used in other fields and discuss how they could be implemented in gifted education research. Finally, we review potential challenges and limitations to implementing collaborative research models in gifted education. We believe greater use of large-scale collaboration will help the field overcome some of its methodological challenges to help provide more precise and accurate information about gifted education.